JAVA LANGUAGE IN THE MADURESE CROSS CULTURE - Kholik Kholik; Muhammad Ridwan; Saptono Hadi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
Indonesian society in general is bilingual. They mastered the first language (B1) of the local language and discussed the second (B2) Indonesian language. There is a small part of the multilingual community, besides mastering BD and BI, also mastering foreign languages. Nevertheless, the mastery process of each language varies according to the development of Indonesian society. Regarding language and culture, the famous adage that has become truism is "language exists and grows in a cultural environment, and cultural values are expressed in a typical manner in the local language" symptoms associated with the occurrence of bilingual societies in Indonesia specifically or in the world at generally, the other one is through language contact. language contact is the influence of one language on another language either directly or indirectly. due to the occurrence of language contact for users of the language is often interferent or transfer arises. A form of language relativity and cultural relativity is a form of sporadic cultural values often revealed at the lexical level. If the relativity of language and cultural relativity are brought into the realm of second language teaching or foreign languages, there will probably be misunderstandings in communication and in the learning process.